PENGAMBILAN KEPUTUSAN PENENTUAN SUMBANGAN PENGEMBANGAN INSTITUSI (STUDI SITUS SMA N 1 SEMARANG) - Listyaningsih , Endang Suyatmi (2011)
The purposes of this research are (1) to describe the characteristic of principal effort in implementation of taking decision of determining of institution development contribution in Senior High School State 1 Semarang, (2) to describe the obstacle characteristic that is faced in taking decision of determining of institution development contribution in Senior High School State 1 Semarang. The research’s kind is qualitative research. This research is conducted in Senior High School State 1 Semarang. The main subjects in this research are principal, teacher and student. Data collection method used interview, observation, and documentation. Data analysis is started from (1) data reduction, (2) data display, and (3) drawing conclusion. Data validity test used credibility, transferability, conformability and dependability. The research’s result shows that (1) principal’s effort in implementation of taking decision of determining of institution development contribution in Senior High School State 1 Semarang is by doing deliberation and consideration in various things especially parents condition. The principal doing problem’s identification about economical situation of parents and solving problem about in ability of parents in paying SPI through phase’s payment and freeing student from the poor family. In taking decree is done by deliberation through internal meeting and pleno meeting with parents. (2) The obstacle that is faced in taking decision of determining of institution development contribution in Senior High School State 1 Semarang is come from parents and management system of SPI. That obstacle is consist of parents who did not agree with the amount of SPI, the programs that is made by principal, the collection of SPI is not at the same time, and also SPI payment is still used manual payment. The payment with manual system is made the school to work twice. The school should appoint a manager officer of institution development contribution to transfer the money in Bank to be saved, and also taking the money from Bank if institution development contribution fund will be used.